(untitled) (Semiárida, 2020)
The native accessions from Rio Grande do Sul of Paspalum nicorae, “28B”, “26A”, “28C”, “26D” and “28E” and the accessions “Azulão” and “Baio” of Paspalum guenoarum were evaluated in order to measure the association of leaves dry matter yield with other traits of interest on these apomictic plants, tested in different years and locations. A completely randomized block design with three replications in two physiographically distinct regions was used. The evaluations of the agronomic traits was made under cuts. Total dry matter yield, leaves dry matter, stems dry matter, leaf: stem ratio, harvest index and number of tillers were determined. Similar correlations were obtained in both locations, with leaves dry matter yield showing the largest magnitude, affecting directly the total dry matter yield. Correlation analysis showed that overall the leaves dry matter and stems dry matter yield form a high and positive correlation affecting the total dry matter yield. The total dry matter yield can be directly used for selection of genotypes in the genus Paspalum.